HEAT CAPACITY OF FERROSILITE, FE2SI2O6 - Cemič L.; Dachs E. (My University, 2006)
The heat capacity of synthetic ferrosilite, Fe2Si2O6, was measured between 2 and 820 K. The physical properties measurement system (PPMS, Quantum Design®) was used in the low-temperature region between 2 and 303 K. In the temperature region between 340 and 820 K measurements were performed using differential scanning calorimetry (DSC). The C p data show two transitions, a sharp λ-type at 38.7 K and a small shoulder near 9 K. The λ-type transition can be related to collinear antiferromagnetic ordering of the Fe2+ spin moments and the shoulder at 10 K to a change from a collinear to a canted-spin structure or to a Schottky anomaly related to an electronic transition. The C p data in the temperature region between 145 and 830 K are described by the polynomial $C_{p} {\left[ {\hbox{J\,mol}^{{ - 1}}\,{\hbox{K}}^{{ - 1}} } \right]} = 371.75 - 3219.2T^{{ - 1/2}} - 15.199 \times 10^{5} T^{{ - 2}} + 2.070 \times 10^{7} T^{{ - 3}} $ The heat content [H 298 – H 0] and the standard molar entropy [S 298 – S 0] are 28.6 ± 0.1 kJ mol−1 and 186.5 ± 0.5 J mol−1 K−1, respectively. The vibrational part of the heat capacitiy was calculated using an elastic Debye temperature of 541 K. The results of the calculations are in good agreement with the maximum theoretical magnetic entropy of 26.8 J mol−1 K−1 as calculated from the relationship 2*Rln5.
Keywords: FERROSILITE; HEAT CAPACITY; MAGNETIC TRANSITION